Optimalisasi Seating Space Layout pada Groovy Space Coffee and Kitchen di Kota Bogor - Zaqia Yuliana Pratiwi; Heni Pratiwi; Hanakayda Khairunnisa; Wawan Oktariza; Tina Nur Ainun (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Groovy Space Coffee and Kitchen is a coffee shop located in the Bogor City area that serves several types of drinks such as coffee and tea and several foods, both snacks and heavy meals. This research aims to optimize the layout of the sitting room at Groovy Space Coffee and Kitchen using the Activity Relationship Chart (ARC) method based on the results of the Total Cleseness Rating (TCR) calculation. The ARC method is used to determine optimal seating space layout arrangements by considering the shape of the room and the available area. Meanwhile, the TCR method is used to overcome potential conflicts in the use of seating space, such as the density of visitors at certain times. The application of these two methods is expected to produce a seating space layout that is efficient, comfortable, and able to better accommodate the number of visitors. The results of this research show that the new layout is more effective and efficient compared to the previous layout with the results showing that the new layout includes additional seating in the outdoor area and also a change in concept from outdoor to semi-outdoor.